Lastniki organizacijske skupnosti - Jančič, Zlatko (Teorija in praksa, 1997)
The question of employee ownership can not be resolved as good or bad simply through the comparison of economic performances. This is especially the case when facing the ambivalent results of several employee ownership schemes. In order to answer this question we must understand some basic mechanisms of organizational cohesion and reasons for employee commitment as well as the importance of employee ownership in a contemporary organization. Our working hypothesis is that employee ownership success depends upon the degree of corporate community building. In order to confirm it we (before conducting an empirical study) firstly describe the phenomenon of corporate communities and secondly, analyze the methods used to build such communities, namely internal marketing relationships processes.
Keywords: corporation; podjetje; organizacijska skupnost; lastniški odnosi; zaposleni; participacija; interni marketing